Effect of surfactant on emulsification in microchannels. (2nd February 2018) - Kovalchuk, Nina M.; Roumpea, Evangelia; Nowak, Emilia; Chinaud, Maxime; Angeli, Panagiota; Simmons, Mark J.H.
Graphical abstract: Highlights: Dynamic interfacial tension (DIT) is a key parameter for controlled drop production. Flow map is invariant in co-ordinates of capillary numbers based on DIT. Size of small drops increases as flow rate ratio to the power 0.1. Size of large drops increases as flow rate ratio to the power 1. Ionic surfactant can facilitate drop coalescence in microchannel. Abstract: Drop formation in a microfluidic flow-focusing device (cross-junction) was studied in absence and presence of one of two ionic surfactants. Four different flow regimes: squeezing, dripping, jetting, and threading were observed in line with existing literature. The effect of surfactant on the transition between flow regimes was shown to depend upon the value of critical micelle concentration and correlates with dynamic surface tension. Drop length in the channel increased as the ratio of flow rate of dispersed to continuous phase, φ, increased. For drops smaller than the channel width, the increase was slow, proportional to φ 0.1, yet was much faster, proportional to φ, for larger drops. In contradiction to the expected stabilisation of drops by surfactant, surfactant-laden drops larger than the channel height coalesced inside the channel at a higher rate than surfactant-free drops. It is proposed that the coalescence is caused by the electrostatic attraction due to surfactant redistribution under the high shear stresses near the wall of the channel.